Focusing techniques and their role in the kinetic formation of the performance of the Iraqi theatrical actor - Waad Abdul Amir Khalaf (Basrah Arts Journal, 2024)
The actor’s focus takes a large part of the kinetic performance and scenic formation after it is a performance technique capable of organizing the space of the theatrical performance, as the focus of the actor takes a means that supports the performance and appears in an acceptable way from the recipient’s point of view. In light of the above, the researcher divided his research topic into four chapters. The first chapter (the methodological framework) included the research problem represented by the following question: What is the role of focus techniques in the kinetic formation of the actor’s performance in the Iraqi theatrical performance? Then access to the importance of the research and the need for it and the research objective which was determined as follows: Identifying the role of concentration techniques in the movement formation of the actor’s performance in the Iraqi theatrical show, in addition to determining the time and place of the research sample and mentioning the terms mentioned in the title text, and the second chapter included two topics, the first: Concentration, its concept, types and tasks, and the second topic was determined under the title: Concentration in the movement actor. Then addressing the paragraph of what the theoretical framework resulted in. The third chapter included the research community and its sample, then determining the methodology that the researcher will follow, represented by the descriptive analytical method, then the research tool that will enable him to analyze the sample, as for the fourth chapter, it was determined by the most important results that the researcher reached through the analysis of the sample, then the conclusions related to the axis of the study, in addition to addressing some recommendations and suggestions to conclude his study with the most important references that he relied on in the facts of the research entitled Concentration techniques in the movement formation of the actor’s performance.